"Un-disabled by Covid": Reflections of a (usually disabled) socio-legal scholar. (17th November 2022) - Williams, Clare
Abstract: We have all been disabled by Covid: routines interrupted, interactions curtailed, access denied. For many, this was new and troubling. For some, though, like me, this was normal life. Charting two years of intermittent lockdowns due to Covid and the remote working practices that emerged, this article chronicles my experiences as a (usually) disabled socio-legal scholar who found themselves included on an equal basis for the first time. Covid leveled the playing field, giving us glimpses into how remote and hybrid working might be harnessed to fully include disabled people in the workplace. Legal research and academia are fields that are generally amenable to remote and hybrid working. And yet, the "back-to-normal" narrative urges a return to the built and social environments that imply "back to exclusion." Additionally, proposals for hybrid or remote working tend to be painted as the choice of the individual—a core neoliberal principle. But for disabled or vulnerable people, an individual choice to work remotely can be neither free nor fair. We risk being segregated once again from society; only this time, the segregation is justified by our individual choice. While disabled communities glimpsed a vision of a more inclusive workplace, narrative trends imply entrenched inequality and the full realization of neoliberal academy.